FEM procedures to study fatigue crack growth in thin coated components. (12th May 2004) - Baragetti, S.; La Vecchia, G.M.
Surface thin coatings are extensively used in applications in which corrosion and wear resistance assume great importance. Physical Vapour Deposition (PVD), Chemical Vapour Deposition (CVD) and electrochemical deposition processes are nowadays used to protect the surface of a lot of mechanical components. Notwithstanding that in the literature there are a lot of papers dealing with surface coatings mechanical characterisation, both via experimental tests and numerical analyses, only in a few papers have studied the fatigue behaviour of coated components. The objective of this paper is to investigate the modalities of numerical modelling of thin electroless Ni-P coated components with the aim of giving a general procedure able to foresee fatigue life.